Vertebrology: recognition (slightly delayed) - Korzh, Oleksey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article elucidates the way of its formation and stages in the development of a new branch of medicine, vertebrology, which unites orthopaedists, traumatologists, neurologists, radiologists, phthisiologists, oncologists, and bonesetters. The contribution made into the solution of this problem by Sytenko Institute (Kharkiv) is shown. Tasks of vertebrology for the near future are outlined.